2022
DOI: 10.1093/ecco-jcc/jjac051
|View full text |Cite
|
Sign up to set email alerts
|

Pain Characteristics in Patients with Inflammatory Bowel Disease: A Monocentric Cross-Sectional Study

Abstract: Background and aims The abdominal pain common in Inflammatory Bowel Disease (IBD) patients is traditionally associated with inflammation but may persist during clinical remission. Central sensitisation (CS) has never been explored in these patients. This study aimed to determine the epidemiology of pain in IBD patients and to specify pain characteristics with special attention to CS. Methods This cross-sectional study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Moreover, alexithymia, and clinical psychological symptoms may compromise patient’s compliance and adherence, leading to frequent relapses and to a worse clinical course of IBD (Viola et al ., 2023 ). Even though IBD affects both genders equally, our study confirmed women with IBD showed higher prevalence of anxiety and depressive symptoms, together with lower HR-QoL (Hardy et al ., 2022 ). Age was also associated with higher anxiety and alexithymia, suggesting a possible explanatory role of chronic fatigue, levels of stress, and persistent abdominal pain even in the remission phase (Villoria et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, alexithymia, and clinical psychological symptoms may compromise patient’s compliance and adherence, leading to frequent relapses and to a worse clinical course of IBD (Viola et al ., 2023 ). Even though IBD affects both genders equally, our study confirmed women with IBD showed higher prevalence of anxiety and depressive symptoms, together with lower HR-QoL (Hardy et al ., 2022 ). Age was also associated with higher anxiety and alexithymia, suggesting a possible explanatory role of chronic fatigue, levels of stress, and persistent abdominal pain even in the remission phase (Villoria et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal pain and fatigue are the most reported concerns of patients with IBD [ 5 , 61 ]. Commonly prescribed drugs for IBD focus on decreasing excess inflammation without effectively managing patients’ pain [ 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea, weight loss, and rectal bleeding are common side effects associated with extensive and long-lasting inflammation. A total of 70% of patients suffering from IBD will report abdominal and rectal pain [ 3 , 4 , 5 ]. This visceral pain (VP) will often dissipate as the patient recovers.…”
Section: Introductionmentioning
confidence: 99%